ANALISIS KESADARAN KESEHATAN DAN KEKHAWATIRAN KEAMANAN PANGAN PADA MAKANAN ORGANIK MEMPENGARUHI NIAT BELI, PERAN MEDIASI KETERLIBATAN KONSUMEN PADA MILENIAL - Alfiansyah, M.; M. Yasser Iqbal Daulay (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2025)
Consciousness of health and food safety continues to increase over time, especially among the millennial generation. This study aims to explore the influence of health consciousness and food safety concerns on purchase intentions mediated by organic food consumer involvement. A quantitative approach and purposive sampling method were used to target respondents who frequently purchase organic food, with a sample size of 190 participants. Data were collected with an online questionnaire designed to measure each variable. The data of the respondents of this study using primary data were processed using the Smart PLS (Partial Least Square) tool. The results showed that health consciousness and food safety concerns have a positive and significant effect on purchase intention, both directly and indirectly through consumer involvement. Consumer involvement proved to be a partial mediator that strengthens the relationship between health consciousness and food safety concerns on purchase intention. These findings provide important implications for marketers of organic products to increase educational campaigns on health and food safety and strengthen consumer involvement in making purchase intentions.